Digital Footprint Metrics and Ranking Outcomes: A Webometric Comparison of Top 10 NIRF-Ranked Universities with Global Indices - Mondal, Debdas (Information Research Communications, 2025)
Background In the contemporary digital era, a university’s online presence has become a critical determinant of its academic reputation and global competitiveness. While Indian universities perform strongly in national assessments such as the National Institutional Ranking Framework (NIRF), disparities persist in their global visibility and international ranking performance. This study aims to examine the relationship between digital footprint metrics and global ranking outcomes of the top 10 NIRF-ranked universities in India, with a focus on understanding how web presence contributes to international recognition. Materials and Methods The study employs a webometric and comparative analytical approach. Data were collected on key digital footprint indicators, including domain authority, number of backlinks, monthly website visits, social media engagement, and a composite Web Visibility Index. Global ranking data were sourced from QS World University Rankings, Times Higher Education (THE), and Webometrics rankings. Descriptive statistics, comparative analysis, and correlation analysis were used to assess the association between digital footprint metrics and global ranking performance. Results The findings reveal a positive and statistically meaningful association between strong digital presence and higher positions in global university rankings. Universities with higher web traffic, stronger backlink networks, and greater social media engagement tend to achieve better visibility in QS, THE, and Webometrics rankings. However, the study also identifies noticeable gaps in digital visibility among certain NIRF top-ranked universities, indicating uneven adoption of effective digital strategies. Conclusion The study concludes that digital footprint plays a significant role in enhancing the global competitiveness of Indian universities. Strengthening web visibility through strategic digital optimisation, open-access dissemination of scholarly outputs, and sustained global online engagement is essential for bridging the gap between national reputation and international recognition. The findings offer actionable insights for policymakers, university administrators, and digital strategy teams to align institutional web presence with global ranking aspirations.
Keywords: Backlinks; Digital Footprint; Domain Authority; Global University Rankings; Higher Education; India; NIRF Rankings; Social Media Engagement; Web Visibility; Webometrics.